Penggunaan Oil Based Mud Pada Proses PemboranMinyak Dan Gas Bumi Pada Sumur X Lapangan Y - Citra Wahyuningrum; M. Mahlil Nasution; Raihan Faturrahman (Jurnal Bhara Petro Energi, 2023)
Water-Based Mud (WBM) and Oil-Based Mud (OBM) are the most commonly used drilling fluids today and both have several different characteristics. Oil Based Mud (OBM) is an oil-based drilling mud consisting of base oil (such as crude oil), emulsifying agent, and additional materials. This study aims to determine the use of oil based mud in the oil and gas drilling process. The research methodology used is literature study, with data collection obtained from related companies, and practitioners who have experience in using OBM. The data obtained was processed qualitatively and quantitatively to determine the use of OBM in the oil and gas drilling process. This study focuses on the use of OBM in the oil and gas drilling process. The purpose of this study is to find out what materials are used in OBM, how to use OBM in the drilling process and to calculate the estimated total cost required for materials for using Oil Based Mud (OBM) in the oil and gas drilling process.The results of the study show that the nominal that must be spent for materials for the manufacture of Oil Based Mud (OBM) in the oil and gas drilling process is  342548,442 USD.